Immediate effect of selective neuromuscular electrical stimulation on the electromyographic activity of the vastus medialis oblique muscle - Denise DalAva Augusto; Paula Pinheiro Ventura; João Felipe de Souza Nogueira; Jamilson Simões Brasileiro (Revista Brasileira de Cineantropometria e Desempenho Humano, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p155